The Archetype as a Heuristic Instrument for the Sociology of the Imaginary - Valentina Grassi (Italian Sociological Review, 2026)
Today, one of the most interesting questions for the sociological discipline, including from the point of view of methodology and method, probably concern the question of the archetype as a heuristic tool. In which way it can be usefully adopted by the sociology of the imaginary - which is gradually making its way into the mainstream discipline and which poses itself as a perspective for understanding the deep, even unconscious, dimension of social phenomena and actions? In this respect, it is useful to look back at some crucial moments in the thinking of authors such as Gilbert Durand and Cornelius Castoriadis, who laid the foundations for an epistemologically and methodologically equipped use of the notion of archetype in contemporary social sciences.